1970
DOI: 10.1152/ajplegacy.1970.218.5.1301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3',5'-GMP and 3',5'-IMP on production of glucose and ammonia by renal cortex

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1970
1970
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…It has been suggested previously that the fall in cortical glutamate provoked by severe metabolic acidosis (4,5), and by exposure of cortical slices to cyclic AMP, cyclic IMP, or 5'-IMP (9,10), is due to the fact that these factors enhance conversion of glutamate to glucose. However, in the present study it was observed that in some experimental situations cortical gluconeogenesis can be altered substantially without an associated inverse change in glutamate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested previously that the fall in cortical glutamate provoked by severe metabolic acidosis (4,5), and by exposure of cortical slices to cyclic AMP, cyclic IMP, or 5'-IMP (9,10), is due to the fact that these factors enhance conversion of glutamate to glucose. However, in the present study it was observed that in some experimental situations cortical gluconeogenesis can be altered substantially without an associated inverse change in glutamate.…”
Section: Resultsmentioning
confidence: 99%
“…Further, although the effect of potassium deficiency on cortical glutamate has not been studied previously, it has been noted that in potassiumdepleted rats there is an increase in cortical gluconeogenesis as well as in ammonia production (3,8). Additional support for the hypotesis has been derived from studies of the effects of 3',5'-adenosine monophosphate (cyclic AMP), 3',5'-inosine monophosphate (cyclic IMP), and 5'-inosine monophosphate (5'-IMP) on the metabolism of cortical slices; these nucleotides, which enhance cortical glucose production, also lower glutamate content and increase production of ammonia from glutamine (9,10).…”
mentioning
confidence: 99%
“…cGMP antagonizes the cAMP stimulated synthesis of flgalactosidase in cell-free bacterial extracts (3,4). In certain animal cells as well, cGMP appears as if it might also directly or indirectly counteract the effects of cAMP (5)(6)(7)(8)(9). We have, therefore, investigated the interaction between these cyclic nucleotides on the pleiotypic reactions and conclude that here, too, cGMP overcomes the actions of cAMP.…”
mentioning
confidence: 94%
“…The reduced ammonia production in alkalosis and after acetazolamide (9) could be caused, to some extent, by cGMP which inhibits ammonia production from glut amine (11). Whether the change of cGMP for mation in relation to alkalosis and acidosis is a part of physiological regulation of intracellular pH remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Since activation of renal adenylate cy clase by acetazolamide has been suggested (14), it was of interest to measure the renal tissue levels of cyclic adenosine 3':5'-monophosphate (cAMP) for their dependence on dosage and time after administration of the diuretic. A possible role of cyclic guanosine 3 ':5 '-mono phosphate (cGMP) in renal acid-base regulation is suggested by Pagliara and Goodman (11) who found in isolated rat kidney cortex slices that cGMP inhibited the formation of a-ketoglutarate from glutamate and decreased ammonia production. Renal bicarbonate reabsorption as well as ammonia production are involved in acid-base regulation and are inhibited by acetazolamidc (9).…”
Section: Introductionmentioning
confidence: 99%